Personal Branding Analysis of @tasyafarasya as a Beauty Influencer on TikTok - Haris, Utari Kencana; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
In the digital age, personal branding is becoming a crucial strategy for individuals who want to highlight their skills and interests on social media. This study aims to analyze the personal branding strategy implemented by Tasya Farasya, a beauty influencer, on the TikTok platform. Using the eight principles of personal branding proposed by Montoya (2002), this study sought to understand how Tasya built and maintained her identity as an influencer in the beauty industry. This study used a qualitative descriptive method, with primary data obtained through observation of the TikTok account @tasyafarasya, in-depth interviews with three of her active followers, and direct interviews with Tasya Farasya to get an in-depth perspective on the personal branding strategy she implemented. The analysis was conducted to evaluate the extent to which the principles of personal branding are applied by Tasya in her activities on social media. The results showed that the principle of specialization, which emphasizes the importance of focusing on one particular area, is dominant in Tasya's personal branding strategy. She consistently presents content focused on beauty and makeup product reviews, which distinguishes her as an authoritative figure in the industry. In addition, Tasya has also successfully implemented other principles such as content consistency, active interaction with followers, and honesty and transparency in product reviews, all of which contribute to increased audience visibility and engagement. The research provides practical insights into how personal branding can be built and strengthened on social media platforms, particularly TikTok, as well as the effectiveness of the strategies used in building relationships and trust with audiences.